2015
DOI: 10.1590/0104-07072015000940014
|View full text |Cite
|
Sign up to set email alerts
|

Nursing perceptions about abortion management and care: a qualitative study

Abstract: ABSTRACT:This study aimed to describe management and implementation of care for women hospitalized due to an abortion, from the perspective of nursing professionals. A qualitative study performed in an obstetric hospital unit of a University Hospital in the extreme South of Brazil, by means of a semi-structured interview with 19 nursing professionals. For the analysis, the Collective Subject Discourse technique was used. The statements were ambivalent. Some nursing professionals reported interference in discri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 11 publications
0
24
0
10
Order By: Relevance
“…The focus group technique was used to obtain knowledge on the experiences of the participants, as pregnant women, when among their peers, feel more comfortable to express their views. This technique provided interaction, facilitated the verbalization of doubts, taboos and prejudices, and the participants also shared opinions, made inferences and sought for solutions to common problems (12) .…”
Section: Methodsmentioning
confidence: 99%
“…The focus group technique was used to obtain knowledge on the experiences of the participants, as pregnant women, when among their peers, feel more comfortable to express their views. This technique provided interaction, facilitated the verbalization of doubts, taboos and prejudices, and the participants also shared opinions, made inferences and sought for solutions to common problems (12) .…”
Section: Methodsmentioning
confidence: 99%
“…It is important to remember that the way in which the multiprofessional team will give the information to the woman may have future repercussions, affecting its subsequent decision-making process (19) . It is essential that the woman feels welcomed and treated with care and respect, while receiving detailed information on the fetus diagnosis and procedure to terminate with pregnancy when desired.…”
Section: Discussionmentioning
confidence: 99%
“…It is up to the health professionals at this moment to act with respect to the decision of the woman to terminate or not the pregnancy. This theme should be approached both during professional training and in training actions of the team so that they know how to act on the problem, not losing the possibility of interacting and clarifying doubts of women, considering the subjectivity of each woman/family when planning care actions (19) . The interdisciplinary health team is also highlighted as a positive aspect, most of the time by women, as they have received help to go through this difficult experience (20) .…”
Section: Discussionmentioning
confidence: 99%
“…16 The profile of health professionals demonstrates insufficient qualification for the needs of women who have had fetal loss, reporting little interaction with women, conducts focused on clinical aspects, and an ambivalent contact between good and discriminatory according to the etiology of fetal loss. 17 The sociodemographic and reproductive characteristics of women in studies covering grief due to fetal death should be included, and it has been observed that social norms according to each country can contribute to the high levels of grief. 12 The different means of the PGS score between the populations of this and other studies with perinatal (m=88±27), 10 and fetal losses (m=91±21), 9 prove that although loss may be a universal experience, its representation and influence on an individual's life are modified by their personality, culture, and society.…”
mentioning
confidence: 99%